The Etiology of Nosocomial Infections in Pediatric Patients at the Department of Child Health, School of Medicine Padjadjaran University Hasan Sadikin General Hospital, Bandung - Herry Garna (Indonesian Pediatric Society Publishing House, 2019)
Tbe distribution of pathogens causing nosocomial gastroenteritis was E. coli (69.2%), Salmonella sp (23.1%), rotavirns (6.4%) and Shigella sp (1.3%) . Klebsiella pneumoniae seemed to be the pathogen most frequently associated with nosocomial skin infections (26. 7%), followed by Enterobacter aerogenes (20.0%), E. coli, Ps. Aeruginosa and S. aureus, each in 13.3% and others 03.4%). Salmonella sp was the pathogen most frequently associated with nosocomial bacteremia (20.2%), followed by Klebsiella sp 07.9%), S. a/bus 04.3%), Enterobacter sp 01.9%), Pseudomonas sp (9.5%), S. aureus (9.5%) and others (16. 7%). In nosocomial urinary tract infections, the result was E. coli (32.9%), Klebsiella pneumoniae (20.5%), Enterobacter sp 03. 7%), Citrobacter diversus (6.8%) and others (26.1%). In general, E. coli was the most frequently reported pathogens ( 42.0%), followed by Salmonella sp 07.1%), Klebsiella sp (10.2%), Citrobacter sp (7.2%), S. a/bus (4.5%), Pseudomonas sp (4.2%), S. aureus (3.6%) and others 01.2%), respectively.